Entrepreneurial Intentions for Engineering Students: Does Entrepreneurship Education and Family Environment Matter? - Agariadne Dwinggo Samala; Ganefri Ganefri; Asmar Yulastri; Yose Indarta; Fadhli Ranuharja; Ika Parma Dewi (Yayasan Keluarga Guru Mandiri, 2022)
This research aims to analyze the influence of entrepreneurship education and family environment on engineering students' entrepreneurial intentions within higher education. This examination method used was associative causal research. The research methodology is based on statistics using multiple regression analysis. This research was conducted on undergraduate students (S1) in the 2020 entry year at the Faculty of Engineering, Universitas Negeri Padang, which consists of 10 different undergraduate study programs. The total population for this research was 654 students. The total sample of this research was 200 students using the purposive sampling technique with the Slovin formula. This study's conclusions revealed that entrepreneurship education and family environment have a practical and remarkable impact on engineering students’ entrepreneurial intentions. Partially, the variables of entrepreneurship education and family environment have a positive and significant impact on engineering students’ entrepreneurial intentions. In conclusion, the results of the hypothesis testing show that entrepreneurship education and family environments have a significant positive effect on engineering students’ entrepreneurial intentions.